Detection of 2-amino-1-methyl-6-phenylimidazo [4,5-b]-pyridine (PhIP)-DNA adducts in human pancreatic tissues - ZHU, JIJIANG (2006)
Recent epidemiologic investigations have observed an association between consumption of grilled or barbequed meat and an increased risk for pancreatic cancer, suggesting that dietary exposure to heterocyclic aromatic amines (HCA) may contribute to the development of this disease. 2-Amino-1-methyl-6-phenylimidazo [4,5-b]-pyridine (PhIP) is the most abundant HCA found in well-done and grilled meats. To determine whether HCA-induced DNA damage is present in the human pancreas, we used immunohistochemistry and computer-assisted image analysis to measure PhIP-DNA adducts in 54 normal pancreatic tissues (N) from persons without pancreatic cancer and in 38 normal adjacent pancreatic tissues (A), and 39 cancer tissues (T) from 68 patients with pancreatic adenocarcinoma. PhIP-DNA adducts were detected in 53 N, 34 A, and 39 T samples. Mean values (±SD) of the absorbency for PhIP staining were 0.22 ± 0.04, 0.24 ± 0.04, and 0.24 ± 0.03 for N, A, and T samples, respectively (p = 0.004). Using the median absorbency (0.21) of the samples from normal controls as the cut-off, 71% of A and 77% of T tissues, compared with 48% of N tissues, were distributed in the higher range (p = 0.009). The odds ratio of pancreatic cancer was 3.4 (95% confidence interval 1.5 to 7.5, p = 0.002) for individuals with a higher level of PhIP-DNA adducts. This is the first report of detection of PhIP-DNA adducts in human pancreatic tissue samples obtained from patients having unknown exposure to HCA. Although limited by the small sample size, these preliminary results suggest that PhIP exposure may contribute to human pancreatic cancer development.